The impact of natural pandemics on the permanence of the decade: Covid-19 crisis in the aviation sector as a model - Al-Hamdani, Khaldoun Mohammed (Al-Adab Journal, 2022)
In our time, we are living in the time of Corona virus, there is an urgent need to activate laws that were forgotten due to the distance of the era of pandemics and epidemics on us. Of the owners of the money their income and many families approached bankruptcy. Our research aims to shed light on the law that can mitigate harm to the citizen, and certainly our research focuses on studying similar cases of bankruptcy and loss of job and income opportunities in developed countries to benefit from its outputs and how to adopt it as compensation for the losses of Corona in our country. Accordingly, it was necessary to shed light on the aspects of the emergency theory that were and still are the lifeline in the investment stricken by the pandemics. The airlines, which are considered one of the most affected sectors, were used as a model to adopt their solutions in situations that Iraq may be exposed to at any time due to the return of the fourth wave of the virus, that virus, which had a devastating impact on life in this millennium.